A Journey to the North Cave and Other Stories: Creating Children’s Picture Books Portraying Bullying towards Children and its Coping Mechanisms to Handle it - Ivana Meyi Liestanto (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This paper presents five children’s picture book stories designed for children aged six to eight to discuss the bullying issue in children, particularly highlighting how the act of bullying happens to children as well as how they deal with the issue. Dorte Marie Søndergaard‘s Process of Bullying in Children and Lazarus and Folkman’s Problem-Focused Coping are used as the theoretical framework. From the first to the fifth story, the main characters–Kim, Ruby, Fillo, Lora, Roo–have either different appearances or behaviors that elicit the bullies to point out their differences and bring them into their conversation which later turns into more serious bullying, such as blatant verbal or physical bullying. To successfully overcome this problem, each of the main characters will use one of a few coping mechanisms which are divided into confrontative coping, planful-problem solving, and social-seeking support.